Study on the characteristic spectral bands of water molecule and hydrogen bond of methane hydrate. (2nd February 2022) - Huang, Xin; Zhang, Le; Cai, Wenjiu; He, Jiayuan; Lu, Hailong
Graphical abstract: Highlights: The evolution of water molecular characteristics during hydrate formation is studied. Quantitative analysis of spectra can reveal the disorder-order character of hydrate. The peak of the hydrogen bond changes abruptly before and after the phase transition. Abstract: In this study, in situ observation on the formation of methane hydrate with a laser confocal Raman imaging microscope is conducted, to reveal the interaction between the guest molecule and the lattice water molecule. The evolutions of the broad band of the stretching vibration of water molecules and intermolecular hydrogen bonds in the Raman spectrum are observed in the course of methane hydrate formation, revealing that quantitative analysis of Raman spectrum can be considered as a criterion of the disorder–order character of the water–hydrate phase transition. Moreover, based on the recognition that the characteristic peak of the hydrogen bond will change abruptly before and after the phase transition, a promising technique is proposed for field hydrate exploration and laboratory identification of hydrate growth.